Moja przygoda z praktycyzmem - Domański, Juliusz (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2016)
For forty years I have been using in all my Polish scientific works the term "practicism" ("praktycyzm"), and its equivalents in my publications in French, German and Italian. This term has its strong background in Aristotle's notion and term of praxis, which was with precision defined in the commentaries to Nicomachean Ethics, in particular, by numerous medieval commentators. However, this term became not to be a popular one – both in colloquial and philosophical languages, although, it was used later by some other Polish historians of philosophy. When I relate today, and once again explain the sense of my studies on practicism, I do it to inspire young philosophers to search the new terms and definitions for better, maybe well-aimed, description of the phenomena and contents, which I called "practicism".
My Adventure With Practicism
Keywords: practicism; Domański; praxis; Aristotle; ancient philosophy; practical philosophy